Hematological And Biochemical Studies On Dermatoses In Canines - Narang, Asmita; Arora, Niddhi; Rajora, V.S.; Mrigesh, Meena; Das, A.K.; Krishan, Gopal (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Estimation of hemato-biochemical profiles revealed significant (P<0.05) decrease in Hb, PCV and TEC and increase in eosinophils in acariasis. Lymphopenia and neutrophilia were observed in mange and pyoderma. Leucocytosis was recorded in all the etiological groups. There was significant increase (P<0.05) in total proteins and globulins and decrease in albumin and A:G ratio in all the etiological groups except bacterial dermatitis. Hypoglycemia in cases of ectoparasitic dermatitis but hyperglycemia in bacterial dermatitis was recorded. Significant increase (P<0.05) in activity of serum enzymes ALT and AST were observed in mange affected dogs.